Persepsi Keluarga Dusun Pablengan Kulon terhadap Urgensi Pendidikan Agama Islam bagi Anak - Alief Nabilah; Mutohharun Jinan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to find out how families in Dusun Pablengan Kulon perceive the urgency of Islamic religious education for children. Apart from that, to find out what efforts families in Dusun Pablengan Kulon have made to obtain Islamic religious education for their children. The research methodology used is field study, namely data collection in the form of observations, interviews, and documentation studies. Data analysis techniques use data reduction, presentation and drawing conclusions. The source of research data is the community in Dusun Pablengan Kulon, Krikilan, Kalijambe, Sragen, Central Java. This hamlet was chosen because it is a model hamlet in other Krikilan Villages. The results of the research show that families in Dusun Pablengan Kulon already understand the urgency of Islamic religious education for children. The results of the second research show that the efforts of families in Dusun Pablengan Kulon to address the urgency of Islamic religious education for children is by providing Islamic religious education at home, providing encouragement to enroll their children in non-formal religious education, namely the Al-Qur'an Education Park (TPQ), and for parents who have full awareness of Islamic religious education and are supported by a stable economy, this will give their children the opportunity to study in an Islamic-based school.